The Relationship between COVID-19 Prevention Measures and Quality of Life for the Elderly with Hypertension during the COVID-19 Pandemic - Zulfitri, Reni; Agrina, Agrina; Husnawati, Husnawati (Fakultas Ilmu-ilmu Kesehatan, 2022)
This study aimed to determine the relationship between COVID-19 prevention measures and the quality of life for the elderly with hypertension during the COVID-19 pandemic. This was a descriptive correlation study that applied a cross-sectional approach that involved 133 respondents who were selected using the convenience sampling technique. Data were collected using questionnaires from the World Health Organization Quality of Life – BREF (WHOQOL-BREF) and COVID-19 prevention measures. The collected data were processed using the Chi-Square test in univariate and bivariate analyses. The results showed that the number of elderly participants who took positive and negative efforts in preventing COVID-19 transmission was almost equal, with a slightly higher number of participants taking positive efforts with a total of 69 people (51.9%). There was also a higher number of elderly participants who had a good quality of life with 71 people (53.4%). The Chi-Squared test results indicated a relationship between COVID-19 prevention measures and the quality of life of elderly patients with hypertension during the COVID-19 pandemic with a p-value of 0.008. Therefore, it can be concluded that prevention efforts in the form of health behaviors for the elderly with certain chronic diseases comorbid with COVID-19 can affect their quality of life.